Design and analysis of compact paddy harvester machine. (2022) - Yogaraj, D.; Subesh, T.; Devaraj, A.; Sree Pranay Chowdary, Kannam; Khakha, Uday; Alone, Santosh P.; Sharma, Abhishek
Abstract: Modern technologies were developed in agricultural industry with vast range of equipment for efficient farming and harvesting process. In meanwhile, the challenging issue is that it is not affordable to the farmers with poor economic background and small-scale farmers who might frequently face the problem of labour shortage. The purpose of this work is to develop a new agricultural machine that fit to various conditions in the agricultural field for harvesting. The machine comprises of a petrol engine of 2 HP (Horsepower), collecting unit, pulley, belt drive, and cutter blades. The crop cutting is being done by a scissoring type of motion where the blade cuts the mature crop and transmit in horizontal position through belt conveyer and then the crop is collected in the collecting tank having a capacity of 0.25 ton. The slider crank mechanism is used to transmit the power to the cutter which is driven by pulley. A collecting unit is provided to collect the harvested crop. The proposed machine shows improved efficiency when compared to traditional and modern methods.